2018
DOI: 10.1145/3299710.3211336
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive deep learning model selection on embedded systems

Abstract: The recent ground-breaking advances in deep learning networks (DNNs) make them attractive for embedded systems.However, it can take a long time for DNNs to make an inference on resource-limited embedded devices. Offloading the computation into the cloud is often infeasible due to privacy concerns, high latency, or the lack of connectivity. As such, there is a critical need to find a way to effectively execute the DNN models locally on the devices. This paper presents an adaptive scheme to determine which DNN m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 42 publications
(52 reference statements)
0
28
0
Order By: Relevance
“…Energy and power optimization for embedded and mobile systems is an intensely studied field. There is a wide range of activities on exploiting compiler-based code optimization [12], [13], runtime task scheduling [14], [15], or a combination of both [7] to optimize different workloads for energy efficiency. Other relevant work in web browsing optimization exploits application knowledge to batch network communications [16], [17], and parallel downloading [18], which primarily target the initial page loading phase.…”
Section: A Energy Optimizationmentioning
confidence: 99%
“…Energy and power optimization for embedded and mobile systems is an intensely studied field. There is a wide range of activities on exploiting compiler-based code optimization [12], [13], runtime task scheduling [14], [15], or a combination of both [7] to optimize different workloads for energy efficiency. Other relevant work in web browsing optimization exploits application knowledge to batch network communications [16], [17], and parallel downloading [18], which primarily target the initial page loading phase.…”
Section: A Energy Optimizationmentioning
confidence: 99%
“…That is, a little and fast model is used to try to classify the input data and the big model is only used when the confidence of the little model is less than a predefined threshold. Taylor et al [103] points out that different DNN models (e.g., MobileNet, ResNet, Inception) reach lowest inference latency or highest accuracy on different evaluation metrics (top-1 or top-5) for different images. Then they propose a framework for selecting the best DNN in terms of latency and accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Predictive Modeling. Recent studies have shown that machine learning based predictive modeling is effective in code optimization [43], [44], performance predicting [45], [46], parallelism mapping [20], [47], [48], [49], [50], and task scheduling [51], [52], [53], [54], [55], [56]. Its great advantage is its ability to adapt to the ever-changing platforms as it has no prior assumption about their behavior.…”
Section: Domain-specific Optimizationsmentioning
confidence: 99%